2022
DOI: 10.3389/fped.2022.944178
|View full text |Cite
|
Sign up to set email alerts
|

Infantile-onset Pompe disease complicated by sickle cell anemia: Case report and management considerations

Abstract: Infantile-onset Pompe disease (IOPD) is a rare, severe disorder of lysosomal storage of glycogen that leads to progressive cardiac and skeletal myopathy. IOPD is a fatal disease in childhood unless treated with enzyme replacement therapy (ERT) from an early age. Sickle cell anemia (SCA) is a relatively common hemoglobinopathy caused by a specific variant in the hemoglobin beta-chain. Here we report a case of a male newborn of African ancestry diagnosed and treated for IOPD and SCA. Molecular testing confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…There are other cases in the literature reporting the association of more than one inherited disorder. Starosta [Starosta et al, 2022] described a case of a child diagnosed with Pompe disease and sickle cell anemia. Lerario [Lerario et al, 2016] reported a boy with Down syndrome and increased CK levels that yielded a co-diagnosis of Becker muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…There are other cases in the literature reporting the association of more than one inherited disorder. Starosta [Starosta et al, 2022] described a case of a child diagnosed with Pompe disease and sickle cell anemia. Lerario [Lerario et al, 2016] reported a boy with Down syndrome and increased CK levels that yielded a co-diagnosis of Becker muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%